CE: A Review of the Revised Sepsis Care Bundles. Issue 8 (August 2018) - Lester, Donna; Hartjes, Tonja; Bennett, Amanda
Abstract : N/A: Sepsis is an extreme response to infection that can cause tissue damage, organ failure, and death if not treated promptly and appropriately. Each year in the United States, sepsis affects more than 1.5 million people and kills roughly 250, 000. Prompt recognition and treatment of sepsis are essential to saving lives, and nurses play a critical role in the early detection of sepsis, as they are often first to recognize the signs and symptoms of infection. Here, the authors review recent revisions to the sepsis care bundles and discuss screening and assessment tools nurses can use to identify sepsis in the ICU, in the ED, on the medical–surgical unit, and outside the hospital. Abstract : An update on recent revisions to the sepsis care bundles, including development of the new one-hour bundle, plus screening and assessment tools nurses can use to identify sepsis in the ICU, in the ED, on the medical-surgical unit, and outside the hospital.